2021
DOI: 10.1111/hsc.13572
|View full text |Cite
|
Sign up to set email alerts
|

How is the environment integrated into post‐stroke rehabilitation? A qualitative study among community‐dwelling persons with stroke who receive home rehabilitation in Sweden

Abstract: Studies have shown a need to consider environmental factors to best support the rehabilitation and recovery process after a stroke. In addition, despite intentions to increase individuals’ participation in care and rehabilitation, patients and family members report weak participation. The aim of this study was to explore how the environment was integrated into rehabilitation at home from the perspective of patients after a stroke. We conducted as a qualitative study with 17 patients rehabilitated at home. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…The selection process is outlined in Fig 1 . Eleven studies were located through database searches, one study through Google Scholar [ 40 ]; one study through the protocol of the study initially found in the database search [ 41 ] and one study retrieved from a conference abstract identified again in the database search [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection process is outlined in Fig 1 . Eleven studies were located through database searches, one study through Google Scholar [ 40 ]; one study through the protocol of the study initially found in the database search [ 41 ] and one study retrieved from a conference abstract identified again in the database search [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were conducted in high income countries as indicated by The World Bank [ 43 ]. Six studies were conducted in the United Kingdom [ 40 , 42 , 44 – 47 ], three studies were conducted in Sweden [ 41 , 48 , 49 ] and one study was conducted in Denmark, Ireland, Canada, Australia and Norway respectively [ 50 54 ]. One study did not analyse data collected via interview, instead analysing responses to open ended survey questions [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, providers need to pay attention to and get involved in an iterative decision-making process that focuses also on daily life and considers the person’s physical and social environment. Earlier studies have shown that this is not the norm in clinical practice today [ 27 ]. In this review, we found one instrument by Masters and colleagues [ 67 ] that could serve as inspiration for future development of instruments in transitional as well as home and community care.…”
Section: Discussionmentioning
confidence: 99%
“…When a patient is informed rather than involved, there is a risk that important information about the patient´s environmental prerequisites will be lost [ 27 ]. For example, inadequate practices of discharge from the hospital—that is, discharge that does not include a dialogue with the patient about his or her home environment and needs post-discharge—may have adverse effects such as dependency in daily activities and social isolation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%